Revisão taxonômica das espécies do grupo Hoplias malabaricus (Bloch, 1794) (Characiformes: Erythrinidae) da bacia do rio da Prata. - Bifi, Alessandro Gasparetto (2013)
With the highest number of species among the Erythrinidae, Hoplias is also the genus of broader geographic distribution. It has taxonomic problems that require a revision of the species of the H. malabaricus group from the La Plata basin. Therefore, morphometric and meristic analyses were performed on specimens from Central and South America. The group was defined as a group of Hoplias species with medial margins of dentary converging toward the mandibular symphysis, four pores of latero-sensory system on each side of the dentary and tooth plates present on the basihial and basibranchials. The valid species belonging to the group are: H. malabaricus, H. microlepis and H. teres, all absent in the La Plata basin. In this review, it was possible to recognize four new species to Science: Hoplias sp. A, distributed in the Paraguay and Paraná rivers; Hoplias sp. B in the upper Rio Paraná; Hoplias sp. C in the Iguaçu and Uruguay rivers; and Hoplias sp. D in the Paraguay, Uruguay and lower Paraná rivers, and another specie not diagnosed by morphology called Hoplias cf. malabaricus in the Paraná and Uruguay rivers. Hoplias sp. B and Hoplias sp. D present the series of scales on the base of the caudal-fin rays forming a rounded margin and 41 or fewer perforated scales in lateral line; H. microlepis, H. teres, Hoplias sp. A and Hoplias sp. C have the series of scales on the base of the caudal-fin rays forming a straight margin and 41 or more perforated scales in lateral line; H. cf. malabaricus has the series of scales on the base of the caudal-fin rays forming a straight margin and 41 or fewer perforated scales in the lateral line. There are two Hoplias species described from the Rio Uruguay basin, Esox tararira Larrañaga, 1923 and Macrodon auritus Valenciennes, 1847 that do not allow recognition as defined and distinct taxonomic entities due to doubts on the existence of type-series and also by lacking information in their original descriptions. Characters in the original description, as numbers of dorsal-, pectoral- and anal-fin rays allow only to recognize them as belonging to the genus Hoplias. In this situation, Hoplias tararira and Hoplias auritus should be considered as nomima dubia.